A prospective study of gout in New Zealand Maoris. Issue 5 (October 1978) - Brauer, G W; Prior, I A
Abstract : Results are reported from the first prospective study of gout in New Zealand Maoris based on a sample of 388 males and 378 females. At baseline, high mean levels of serum uric acid (SUA) were found, 0.422 +/- 0.092 mmol/1 (7.05 +/- 1.54 mg/100 ml) in males and 0.350 +/- 0.091 mmol/1 (5.85 +/- 1.52 mg/100 ml) in females. On the basis of traditional criteria (SUA above 0.42 mmol/1 (7.0 mg/100 ml) in males and above 0.36 mmol/1 (6.0 mg/100 ml) in females) the prevalence of hyperuricaemia was 49% in males and 42% in females. The baseline prevalence of gout (8.8% for males and 0.8% for females) and the subsequent 11-year incidence rates (10.3% for males and 4.3% for females) are discussed in relation to specified SUA classes. When traditional, sex-specific criteria for hyperuricaemia were used, no relationship was found between the prevalence of hyperuricaemia and the incidence of gout. There was, however, a sharp increase in the incidence rate of gout in both sexes when SUA levels were above 0.48 mmol/1 (8.0 mg/100 ml). In subjects with a baseline SUA above this level, the age-standardised 11-year incidence rate of gout was 29.1% for males and 37.2% for females. A previously unreported relationship linking muscle size to the incidence of gout in males is presented as a major finding of the study. Other risk factors associated with gout were body mass and blood pressure.